Symbiosis of intermodal terminals and free zones - Simonovic, Aleksandar; Kostić, Dragan (Serbian Journal of Management, 2023)
Globalism is entering a new phase that creates space for regional investments. The trend of offshoring is beginning to weaken and trend of nearshoring investments are increasing. Jobs and new investments are returning to regions, neighboring countries and parent companies.The new course of development requires the need for spaces where investors will receive customs and tax benefits with a greater need for efficient logistics. Free zones, which offer facilities for investment and business, will have to pay more attention to efficient logistics.The benefits of infrastructure-equipped land, exemptions from paying customs duties and taxes with built-in capacities for intermodal transport, along with other state support measures, will additionally make certain locations attractive for investors.The paper proposed a model of symbiosis of logistics centers and free zones, as well as analyzed instruments that should be used in order to create efficient centers that enable savings in business for future investors
Keywords: logistics centers; global supply chain; free zones